Userinterface analysis on the website of pt. Rifan financindo palembang futures using the usability scale system method - Nova Skorvio Nasari; Apriansyah (Yayasan Pendidikan Rafisqy Arfadhia, 2022)
Website of PT. Rifan Financindo Berjangka has a home link, Profile (History, Products, Client Registration, Brokerage Representatives, Legality, Investment Procedures, Education, Info and activities, Market Updates, Announcements, Contacts, and Location). Service quality in disseminating information on the website of PT. Rifan Financindo Berjangka has become a very important need for the community, because it has an impact on public satisfaction with the performance of information service managers on the PT. Rifan Financindo Futures. In the end, the improvement in service quality is an indicator of the success of PT. Rifan Financindo Berjangka in improving the services provided to the public as well as being a publication media for the PT. Rifan Financindo Berjangka.